Stomatognathic evaluation at five years of age in children born premature and at term - Almeida Guedes, Kildane Maria; D'Avila Nery Guimaraes, Alzira Maria; Bastos, Alliny de Souza [UNESP]; Mesquita Salviano, Karoline Guedes; Sales, Neuza Josina; Doria Almeida, Maria Luiza; Gurgel, Ricardo Queiroz (Biomed Central Ltd, 2015)
Background: The high frequency of alterations of the stomatognathic system associated with premature birth may suggest that prematurity is an important risk factor in the development of this system. Prematurity has an incidence between 6-11% of births and is associated with factors such as genetic, maternal conditions (obstetric problems, nutritional status, infections) and antenatal care. In addition, undesirable situations, such as changes in enamel and the development of the skeletal structure, also appears to be associated with prematurity. This study aimed to look for changes in the stomatognathic system at five years of age associated with premature birth. Methods: We estimated the prevalence of developmental disorders of the stomatognathic system in the primary dentition of preschool children at five years of age. Changes in preterm infants (n = 32) compared with term born (n = 381) were evaluated. Clinical examinations and questionnaire with sociodemographic and health of mothers and children information. Gestational age, birth weight, head circumference, Apgar score and mechanical ventilation, were collected from the medical records to birth records. The explanatory variable was preterm (< 37 weeks gestational age). Results: Results: Prevalence of 7.7% of preterm infants was found. Of these, 40.6% had atresic palate, 56.2% malocclusion and 21.8% enamel hypoplasia. Forty (9.6%) children were not breastfed at the breast, and 26 (65.0%) had some type of malocclusion, showing association between not breastfeeding with an abnormal development of the stomatognathic system. The group of preterm infants showed five times more changes in head circumference and three times more mechanical ventilation use at birth. Change in head circumference at birth and mechanical ventilation has a significant association between groups of preterm and term infants. Conclusions: Mechanical ventilation at birth directly contributed to an increased risk of developmental disorders of the stomatognathic system in preterm infants, especially dental hypoplasia. Non-breastfed children had a higher risk of developing malocclusion. Alterations in head circumference were related effective on dental malocclusion. The results suggest that changes in the stomatognathic system are influenced by premature birth and points to the imperative need of using methods of preventive.
Keywords: Dental Enamel Hypoplasia; Dentition; Primary; Prematurity; Palate; Malocclusion